2015
DOI: 10.17533/udea.rccp.v28n4a01
|View full text |Cite
|
Sign up to set email alerts
|

Edible mushroom powder (Agaricus bisporus) and flavophospholipol improve performance and blood parameters of broilers

Abstract: (Received: January 13, 2015; accepted: June 12, 2015) doi: 10.17533/udea.rccp.v28n4a01 Summary Background: flavophospholipol is an antibiotic growth promoter (AGP). The current ban of AGP in some countries is controversial because their benefits on the environment and economy by saving feed and reducing nitrogen excretion have been overlooked. White button mushrooms have important nutritional properties and the industry discards large quantities of waste that could be fed to animals. Objective: to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
1
16
2
Order By: Relevance
“…Another study (32) found that Flavomycin may induce a high-level response of the antibody to NDV, yet it did not affect the development of immunoglobulins relative to the birds in the control group. According to (7), supplementation with 2% mushroom extract could reduce the antibody titer against ND but, could increase antibody titers against the Avian Influenza (AI) virus. The latter result suggests a reinvestigation of antibody titers with the inclusion of OMW in broilers' diets.…”
Section: Blood Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study (32) found that Flavomycin may induce a high-level response of the antibody to NDV, yet it did not affect the development of immunoglobulins relative to the birds in the control group. According to (7), supplementation with 2% mushroom extract could reduce the antibody titer against ND but, could increase antibody titers against the Avian Influenza (AI) virus. The latter result suggests a reinvestigation of antibody titers with the inclusion of OMW in broilers' diets.…”
Section: Blood Parametersmentioning
confidence: 99%
“…Mushroom waste in the poultry industry could be a suitable replacement for antibiotics (6). It is available from mushroom farms, and possesses prebiotic, antimicrobial, antifungal, and antioxidant properties (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mushrooms have antioxidant, immunostimulatory, anti-inflammatory, antibacterial, antiviral and hypocholesterolemic effects on broiler chickens (BEDERSKA-ŁOJEWSKA et al, 2017). SHAMSI et al (2015a) reported that dietary 20 g/kg A. bisporus improved body weight gain, feed conversion ratio, and reduced serum cholesterol level in broiler chickens. Moreover, dietary inclusion of 20 g/kg A. bisporus increased Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, poultry producers are constantly pursuing solutions to enhance intestinal health, improve laying performance, and extend the laying period in aged laying hens. Feeding poultry various microorganisms to enhance intestinal health and thus improve performance is one strategy that has attracted prominent attention ( Shamsi et al., 2015 , Forte et al., 2018 , Özsoy et al., 2018 , Adetunji and Adejumo, 2019 ).…”
Section: Introductionmentioning
confidence: 99%